2004
DOI: 10.1080/00365520410008141
|View full text |Cite
|
Sign up to set email alerts
|

Valid symptom reporting at upper endoscopy in a random sample of the Swedish adult general population: the Kalixanda study

Abstract: The upper endoscopy survey strategy was successful. The response rate was high and there was no major selection bias of clinical relevance. The cohort selected for this study appears to be representative of the general Swedish adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
126
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(130 citation statements)
references
References 17 publications
2
126
1
1
Order By: Relevance
“…Relationships between age and gastrointestinal symptoms have been previously reported. 3,22 However, different studies have found different relationships between ageing and the prevalence of UGI symptoms, with some studies finding an increasing prevalence with age until the age of 69 or 55 years, from which point the trend was reversed, 3,13 whereas in the Kalixanda study the prevalence decreased even for subjects above 34 years, 23 and others who did not report an association of GER symptoms with age. 24 The reasons for the variation between studies and countries, in this relationship among ageing and UGI symptoms, are still unknown and need to be elucidated further.…”
Section: Discussionmentioning
confidence: 93%
“…Relationships between age and gastrointestinal symptoms have been previously reported. 3,22 However, different studies have found different relationships between ageing and the prevalence of UGI symptoms, with some studies finding an increasing prevalence with age until the age of 69 or 55 years, from which point the trend was reversed, 3,13 whereas in the Kalixanda study the prevalence decreased even for subjects above 34 years, 23 and others who did not report an association of GER symptoms with age. 24 The reasons for the variation between studies and countries, in this relationship among ageing and UGI symptoms, are still unknown and need to be elucidated further.…”
Section: Discussionmentioning
confidence: 93%
“…The invitation included information of the study design and of the aims of the study and a validated questionnaire, the Abdominal Symptom Questionnaire (ASQ) to be returned by mail [15]. Up to two remainders were sent when necessary; 140 subjects were unavailable at the time for invitation, thus 2,860 of the original study population were eligible for inclusion [14]. The overall response rate was 74.2% (n=2,122) of the eligible study population.…”
Section: Study Design and Logisticsmentioning
confidence: 99%
“…Every seventh adult (n=3,000) from the target population (18-80 years of age, n=21,610 in September 1998) was drawn. The sampled subjects were given an identification number (1-3,000) in a random order [14]. …”
mentioning
confidence: 99%
See 2 more Smart Citations